Application of choice experimental design to estimate the willingness to pay of household for reducing air pollution from transport sector in Klang Valley, Malaysia - Sarabdeen, Masahina; Afroz, Rafia; Duasa, Jarita; Mohamad, Noorihsan (2011)
The rapid increase in motor vehicles in Klang Valley, Malaysia would trim down the air quality in urban areas. Thus, it is critically important to reduce the air pollution due to its adverse human health effects. The present study aims to estimate the willingness to pay of the household for reducing the air pollution in Klang Valley, Malaysia as a result of implementation of two types of hypothetical policy options. Choice Experimental Design was used to estimate the willingness to pay of household for avoiding the ill health risks related with air pollution in Klang Valley. The survey result was analyzed using Conditional Logit Model. Three variables; air pollution index, medical expenditure and sick days are significantly influencing on willingness to pay of households in Klang Valley, Malaysia. The household respondents are willing to pay on average between RM 0.32- RM 0.82 per liter of transport intended fuel for reducing the air pollution in Klang valley, Malaysia. The findings obtained from this study hope to provide important insights